Efektivitas Penggunaan Antihipertensi Pada Pasien Diabetik Nefrotik - Anisa Dwirizky Abdullah; Nurpatwa Wilda Ningsi; Riska Mayangsari; Aulia Rahmi Latif (KOLONI, 2023)
Nephropathy diabetic is a microvascular complication of diabetes, which can lead to end-stage renal disease (ESRD) in both type 1 and type 2 diabetes mellitus. Management of hypertension in ND significantly contributes reducing effect of cardiovascular morbidity and mortality, as well as inhibiting the development of kidney damage. This study was an analytical observational study with prospective and retrospective cohort design using comparative study between amlodipine, the combination of amlodipine valsartan and the combination of amlodipine telmisartan in ND at Dr. Wahidin Sudirohusodo Hospital, Makassar which aimed to obtain a comparison of treatment effectiveness. Treatment’s effectivity was measured based on the average decrease in blood pressure while the quality of life in cost utility analysis was measured by the Short Form-36 (SF-36). Sampling was done by purposive sampling technique and obtained 62 samples. The results showed that the combination amlodipine valsartan had better effectiveness than using amlodipine-valsartan and amlodipine alone in reducing systolic blood pressure and diastolic blood pressure for nephropathy diabetic. Keywords: Hypertension, Nephropathy diabetic, blood pressure